Letramento científico: avaliações de engajamento no gênero dissertação de mestrado - Silva, Gerlylson Rubens dos Santos (2023)
Located in the field of Applied Linguistics (AL), the present work aims to verify the state of scientific literacy skills of Basic Education teachers, who work as students in postgraduate programs, based on assessment choices by Engagement (MARTIN; WHITE, 2005), expressed in his Master's dissertations. The study anchors its epistemological assumptions in the fields of scientific literacy (MILLER,1983; OSBORNE, 2002; SANTOS, 2007) and the Appraisal System (MARTIN; WHITE, 2005), the former as an object to be investigated, and the latter as an instrumental resource for analyze. In the field of Appraisal System, the analytical choice of the research focused on the Engagement subsystem, in view of providing the set of linguistic categories that function as a measurement scheme for the degree of authorial responsibility that the textual producer instantiates, through his lexicogrammatical choices. The methodological procedures of the study come together in four distinct stages. The first focuses on the organization of the research corpus, represented by Professional Master's dissertations, from the disciplinary axes of Portuguese Language, Foreign Language, Arts, History, Geography, Philosophy, Biology, Physics, Chemistry and Mathematics. The second moment is associated with the identification of all monoglossic and heteroglossic assessments present in the introductory section of the dissertations. Thirdly, the assessments were analyzed and interpreted, according to the dialogical choices established in the texts, observing valorations approximations and departures from the perspective of each area of knowledge. Finally, the verification of the levels of scientific literacy demonstrated in the productions was carried out, through the verification of the authorial positions caught through the marks that demonstrate the assessment style of each set of the disciplinary axes of the corpus. The study demonstrated that the curricular components Portuguese Language, Foreign Language, History and Philosophy present a linguistic behavior that leads them to classifications that are adequate to the best conditions of scientific literacy, while the disciplines of Arts, Chemistry, Physics, Biology, Mathematics and Geography resulted in productions that behave closer to the intermediate parameters. The investigation presents data on questions of authorship, with emphasis on the articulatory relationships between the discursive voices, as well as on the depth of authorial responsibility that the subject inscribes in his production through valorations instantiated by lexicogrammatical choices. In addition, it presents an outline that discusses the levels of scientific literacy and its specificities found in texts produced under institutionalized conditions of promotion of literate practices in scientific circumstances.